Correlation Between Educational Degrees and Community Employment in Malaka Regency - Syahrul, Syahrul; Nurdin, Nurdin; Tang, Baco; Beni, Wahid Hasyim Tra; Kiko, Burhan; Idris, Idris (Sociology Department Of Syiah Kuala University, 2023)
This study aimed to determine the relationship between education level and community employment and the impact of education level on community employment in Malaka Regency. This research was a qualitative method which aimed to understand in depth the relationship between education level and occupation. The subjects in this study were parents and scholars around 16 people. Data were collected through observation, interviews and documentation. Data analysis included data collection, data reduction, data presentation, and conclusion. The research shows that there is a relationship between education level and employment. This is because those who have a higher level of education do not have job opportunities that match their skills due to limited job opportunities and low incomes. Meanwhile, those with low levels of education have better job and career opportunities as well as higher incomes. They work based on ability and business intention, that are not based on specific skills or expertise. This affects those who graduated from higher education who do not have a job because they do not have the economic capital to make a business. Meanwhile, those who only had an elementary school education were elected as Village Secretaries.